2017
DOI: 10.5194/hess-2017-259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple Causes of Nonstationarity in the Weihe Annual Low Flow Series

Abstract: Abstract:16 Under the background of global climate change and local anthropogenic activities, multiple 17 driving forces have introduced a variety of non-stationary components into low-flow series. This 18 has led to a high demand on low-flow frequency analysis that considers nonstationary conditions 19 for modeling. In this study, a nonstationary framework of low-flow frequency analysis has been 20 developed on basis of the Generalized Linear Model (GLM) to consider time-varying distribution 21 parameters. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…However, there is no such restriction in GAMLSS, allowing time series modeling for observations with any underlying distribution (Rigby & Stasinopoulos, ). Because of its ability to relate time series variables with external covariates, GAMLSS has been employed by many studies for nonstationary modeling and attribution (Jiang et al, ; López & Francés, ; Tan & Gan, ; Villarini, Smith, et al, ; Villarini et al, , ; Xiong et al, ; Zhang et al, , ). GAMLSS has also been used for stochastic simulation of climate variables and in weather generators (Chun et al, ; Serinaldi & Kilsby, , ; Tye et al, ; Verdin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no such restriction in GAMLSS, allowing time series modeling for observations with any underlying distribution (Rigby & Stasinopoulos, ). Because of its ability to relate time series variables with external covariates, GAMLSS has been employed by many studies for nonstationary modeling and attribution (Jiang et al, ; López & Francés, ; Tan & Gan, ; Villarini, Smith, et al, ; Villarini et al, , ; Xiong et al, ; Zhang et al, , ). GAMLSS has also been used for stochastic simulation of climate variables and in weather generators (Chun et al, ; Serinaldi & Kilsby, , ; Tye et al, ; Verdin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…As the largest tributary of the Yellow River, the Weihe River is located on the southern edge of the Loess Plateau and the northern edge of the Qinling Mountains in central China (Chang et al, 2015; Ji and Duan, 2019; Xiong et al ., 2018). The river originates from Weiyuan and joins the Yellow River at Tongguan, with a total length of 818 km, and flowing through three provinces, that is, Gansu, Ningxia and Shaanxi.…”
Section: Introductionmentioning
confidence: 99%
“…The river originates from Weiyuan and joins the Yellow River at Tongguan, with a total length of 818 km, and flowing through three provinces, that is, Gansu, Ningxia and Shaanxi. The Weihe River covers a drainage area of 134,800 km 2 involving 33°42′–37°20′ N, 104°18′–110°37′ E (Xiong et al ., 2018). The mean natural runoff of 10.4 × 10 9 m 3 accounts for 17.3% of total annual runoff of the Yellow River (Yang et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al () investigated the propagation from meteorological to hydrological drought and found El Niño Southern Oscillation and Arctic Oscillation strongly impact the propagation time in the Wei River Basin. Xiong, Xiong, Chen, Xu, and Li () developed a nonstationary low‐flow distribution using eight indices derived from the climate and catchment conditions as candidate explanatory variables on basis of the generalized linear model. The above‐cited studies found that the temporal variability of low‐flow regimes can be explained by climate indices and catchment conditions to some degree.…”
Section: Introductionmentioning
confidence: 99%